2017
DOI: 10.1016/j.addbeh.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

The intervening role of urgency on the association between childhood maltreatment, PTSD, and substance-related problems

Abstract: A range of risk factors lead to opioid use and substance-related problems (SRP) including childhood maltreatment, elevated impulsivity, and psychopathology. These constructs are highly interrelated such that childhood maltreatment is associated with elevated impulsivity and traumarelated psychopathology such as posttraumatic stress disorder (PTSD), and impulsivity—particularly urgency—and PTSD are related. Prior work has examined the association between these constructs and substance-related problems independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Psychological trauma, including physical, mental, emotional, and sexual abuse, has also been shown to increase the likelihood of developing a substance use disorder (Mirhashem, et al, 2017, Conroy, Degenhardt, Mattick, & Nelson, 2009Daigre et al, 2015;Dube et al, 2013;Heffernan et al, 2000), with just one additional traumatic event increasing a person's chances of developing a substance use disorder by 40% (Dube et al, 2013). Various studies have shown that the presence of emotional and physical abuse are the strongest predictors of developing a SUD, especially in men (Mirhashem, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Psychological trauma, including physical, mental, emotional, and sexual abuse, has also been shown to increase the likelihood of developing a substance use disorder (Mirhashem, et al, 2017, Conroy, Degenhardt, Mattick, & Nelson, 2009Daigre et al, 2015;Dube et al, 2013;Heffernan et al, 2000), with just one additional traumatic event increasing a person's chances of developing a substance use disorder by 40% (Dube et al, 2013). Various studies have shown that the presence of emotional and physical abuse are the strongest predictors of developing a SUD, especially in men (Mirhashem, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological trauma, including physical, mental, emotional, and sexual abuse, has also been shown to increase the likelihood of developing a substance use disorder (Mirhashem, et al, 2017, Conroy, Degenhardt, Mattick, & Nelson, 2009Daigre et al, 2015;Dube et al, 2013;Heffernan et al, 2000), with just one additional traumatic event increasing a person's chances of developing a substance use disorder by 40% (Dube et al, 2013). Various studies have shown that the presence of emotional and physical abuse are the strongest predictors of developing a SUD, especially in men (Mirhashem, et al, 2017). Notably, while the experience of traumatic events in an individual's life can make him or her more susceptible to developing any SUD (Boscarino et al, 2010;McCauley et al, 2014), prescription opioid use, specifically, has been associated with higher scores on inventories measuring PTSD symptoms (Meier, Lambert-Harris, McGovern, Xie, & McLeman, 2014 Further, though trauma can occur at any point during a patient's life, the most marked effects are shown when traumatic events occur during childhood (Conroy et al, 2009;Dube et al, 2013;Heffernan et al, 2000;Barahmand, Khazaee, & Hashjin, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the diagnostic manual of the American Psychiatric Association, PTSD is a psychiatric disorder that can occur in people who have experienced or witnessed a traumatic event such as a natural disaster, a serious accident, a terrorist act, war/combat, rape, or other violent personal assault [2]. The 4 key symptoms of PTSD include: intrusion symptoms associated with the traumatic event(s); persistent avoidance of stimuli associated with the traumatic event(s) [3]; negative alterations in cognitions and mood associated with the traumatic event(s); and, marked alterations in arousal and reactivity associated with the traumatic event(s) [4]. Because of the higher incidence of PTSD after encountering a traumatic event [5] and the accompanying possibilities of serious detriments to the individual, family and society, this condition has become a popular topic for psychiatric and clinical psychological research in recent years [6].…”
Section: Introductionmentioning
confidence: 99%